ADAM9 expression promotes an aggressive lung adenocarcinoma phenotype - Céline Mongaret Kossmann; Maxime Annereau; Audrey Thomas-Schoemann; Carole Nicco-Overney; Christiane Chéreau; Frédéric Batteux; Jérôme Alexandre; François Lemare (Tumor Biology)
A disintegrin and metalloproteinase 9 (ADAM9) possesses potent metastasis-inducing capacities and is highly expressed in several cancer cells. Previous work has shown that ADAM9 participates in the adhesive–invasive phenotype in lung cancer cells in vitro. In this study, we evaluated whether ADAM9 expression plays a critical role in metastatic processes in vivo and in angiogenesis. We first found that high ADAM9 expression was correlated with poor lung adenocarcinoma patient prognosis on Prognoscan data base. In vivo model based on intravenous injection in nude mice showed that a stable downregulation of ADAM9 in A549 (TrA549 A9-) cells was associated with a lower number of nodules in the lung, suggesting lower potentials for extravasation and metastasis. On a subcutaneous xenograft we showed that TrA549 A9− produced significantly smaller tumours and exhibited fewer neovessels. In addition, in vitro human umbilical vein endothelial cells exposed to supernatant from TrA549 A9− could reduce the formation of more vessel-like structures. To further understand the mechanism, a human antibody array analysis confirmed that five cytokines were downregulated in TrA549 A9− cells. Interleukin 8 was the most significantly downregulated, and its interaction with CXCR2 was implicated in angiogenesis on an in vitro model. These results emphasize the critical influence of ADAM9 on lung cancer progression and aggressiveness. ADAM9 should at least be a marker of cancer aggressiveness and a potential therapeutic target for cancer treatment.